PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROTATING TRIO EXCNHANGE (RTE) BERBANTUAN MEDIA COUPLE CARD PADA SUB MATERI TATA NAMA SENYAWA HIDROKARBON TERHADAP HASIL BELAJAR SISWA KELAS XI IPA SMA ADISUCIPTO SUNGAI RAYA - Maghfiratul Rahmi; Fitriani Fitriani; Dedeh Kurniasih (Universitas Muhammadiyah Pontianak, 2018)
The background of this research is lack of student’s learning to the tenth grade students of SMA Adisucipto Sungai Raya, due to the less of student’s comprehension especially about concept of compound hydrocarbon system. Therefore, it was needed the method of learning to increase the student’s comprehension about appropriate concept with characteristic both of the subject and student. The aim of this research was to know the differences of student’s learning and the increasement of student’s learning by using cooperative learning method type RTE in chapter of compound hydrocarbon system with couple card. The kind of this research was Pre-Experimental one group pre-test and post-test design research with subjects of this research were thirteen students from grade XI IPA of SMA Adisucipto Sungai Raya. The technique and the instrument to collect the data was using student’s learning test, observation, and interview. The result of data analysis showed the mean score of pre-test was 27,21 and the mean score of post-test was 75,86. The statistic result of Wilcoxon showed that the score was 0,01 less than α (0,01 < 0,05) that mean there were the differences of student’s learning and the influence of student’s learning by using cooperative learning method type RTE with couple card. The increasement of student’s learning was known by counting the gain score of 0,66 in medium score categorize. In this case, the cooperative learning method type RTE with couple card can be used in chapter of compound hydrocarbon system to increase the student’s learning.Keywords: Couple Card, Rotating Trio Exchange (RTE), Compound Hydrocarbon System